Four-Year-Old's Online Versus Face-to-Face Word Learning via eBooks - Escudero, Paola; Pino Escobar, Gloria; Casey, Charlotte G.; Sommer, Kristyn (Frontiers in Psychology, 2021)
Developmental research typically relies on face-to-face testing at laboratories, childcare centres, museums or playgroups. Current social distancing measures have led to a halt in research. Although face-to-face interaction is considered essential for research involving young children, current technology provides viable alternatives. This paper introduces an accessible, replicable and easy to follow method to conduct online developmental research with young children employing a word-learning task as an exemplar, including a detailed workflow and step-by-step guide to using easily accessible programs and platforms. Four-year-old children’s (N=56) performance on a word-learning task delivered online versus face-to-face is provided as a method validation. Children’s performance on the word-learning task was predominantly consistent across delivery modes, with only slight variation in performance between modes. The implications of these similar results across face-to-face and online methods are discussed alongside avenues for further research. Importantly, this paper presents an emerging methodological approach for the online administration of developmental science both within and beyond the COVID-19 pandemic, adding a new tool to current and future developmental scientist’s toolkits.